A phase I trial of panobinostat (LBH589) in patients with metastatic melanoma. (17th October 2016) - Ibrahim, Nageatte; Buchbinder, Elizabeth I.; Granter, Scott R.; Rodig, Scott J.; Giobbie‐Hurder, Anita; Becerra, Carla; Tsiaras, Argyro; Gjini, Evisa; Fisher, David E.; Hodi, F. Stephen
Abstract: Epigenetic alterations by histone/protein deacetylases (HDACs) are one of the many mechanisms that cancer cells use to alter gene expression and promote growth. HDAC inhibitors have proven to be effective in the treatment of specific malignancies, particularly in combination with other anticancer agents. We conducted a phase I trial of panobinostat in patients with unresectable stage III or IV melanoma. Patients were treated with oral panobinostat at a dose of 30 mg daily on Mondays, Wednesdays, and Fridays (Arm A). Three of the six patients on this dose experienced clinically significant thrombocytopenia requiring dose interruption. Due to this, a second treatment arm was opened and the dose was changed to 30 mg oral panobinostat three times a week every other week (Arm B). Six patients were treated on Arm A and 10 patients were enrolled to Arm B with nine patients treated. In nine patients treated on Arm B, the response rate was 0% (90% confidence interval [CI]: 0–28%) and the disease‐control rate was 22% (90% CI: 4–55%). Among all 15 patients treated, the overall response rate was 0% (90% CI: 0–17%) and the disease‐control rate was 27% (90% CI: 10–51%). There was a high rate of toxicity associated with treatment. Correlative studies suggest the presence of immune modifications after HDAC inhibition. Panobinostat is not active as a single agent in the treatment of melanoma. Further exploration of this agent in combination with other therapies may be warranted. Abstract : Panobinostat is not effective in the treatment of metastatic melanoma as a single agent. Histone deacetylases (HDAC) inhibition appears to have an effect on the immune microenvironment which may guide future combination therapies.